Design of a latching mechanism for perching UAVs - Koh, Martin Wei Xiang. (2011)
A major problem for current Unmanned Aerial Vehicles (UAV) used for surveillance is the fact that they do not carry an unlimited power source, and can only remain on station for a fixed period of time. One solution is to learn from nature and get the UAVs to perch on objects like tree branches, like how birds often do that to rest. This would enable them to observe a certain spot for a significantly longer time.This report is the result of work done by three people, with each person taking up the task of design, development and testing, as well as a summary of the work done by other graduate students on the aerodynamics of perching. It is also part of a bigger effort looking into perching UAVs. It describes the design of two concepts that can be used by UAVs to land and hang on to tree branch like objects, like a pole. The designs were also built and tested to verify the concepts’ validity.